Clinical presentation, treatment and outcome of canine malignant mesothelioma: A retrospective study of 34 cases. (25th October 2021) - Moberg, Hanne Larsen; Gramer, Irina; Schofield, Imogen; Blackwood, Laura; Killick, David; Priestnall, Simon L.; Guillén, Alexandra
Abstract: Canine malignant mesothelioma (CMM) is a rare and aggressive tumour associated with a poor prognosis. Limited information is available regarding effective treatment options and prognostic factors. The purpose of this retrospective case series was to describe the clinical presentation, treatment and survival in a cohort of dogs with this disease and to investigate possible prognostic factors. Thirty‐four dogs were included. Tachypnoea and dyspnoea due to pleural effusion were the most common presenting clinical signs. Twenty‐two dogs had a subcutaneous access port placed and 25 dogs were treated with intracavitary and/or intravenous chemotherapy. The main protocols used were single‐agent 5‐FU ( n = 14) and carboplatin single‐agent or alternated with mitoxantrone ( n = 10). The overall response rate (defined as more than 25% reduction in effusion volume) to chemotherapy treatment was 37% after 3‐weeks and 24% after 15‐weeks. The median survival time (MST) for all dogs was 195 days (95% CI 53–324). MST was 234 days for dogs receiving chemotherapy and 29 days for dogs not receiving chemotherapy. The 1‐year survival rate was 22% for all dogs. Treatment with chemotherapy was the only significant prognostic factor associated with survival ( p = .001). Further studies are needed to determine the optimal treatment approach for malignant mesothelioma in dogs. Nevertheless, effusion recurrence should be expected and the prognosis for these patients in the long‐term is poor.